Critical Thinking Competence as regard of Self-Concept and Gender Differences - Sadikin, Sadikin; Fahinu, Fahinu; Ruslan, Ruslan (Malikussaleh Journal of Mathematics Learning (MJML), 2019)
The study was a qualitative research that focused to describe students’ critical thinking competence in mathematics. The subjects were six students from the X MIA-2 class of SMA 11 Kendari consisted of one male student categorized has a high self-concept, one male student categorized has a moderate self-concept, one male student categorized has a low self-concept, one female student categorized has a high self-concept, one female student categorized has a moderate self-concept, and one male student categorized has a low self-concept. In collecting data, the researcher used test instrument and questionnaire which were critical thinking competence test and self-concept questionnaire. Furthermore, the data collected were analyzed based on five phases of students’ critical thinking ability in mathematics. The result of the study revealed that male students had better critical thinking abilities than female students. A better self-concept category will contribute to enhance student’s critical thinking in mathematics